Preliminary study on coexistence with the Covid-19 based on the Theory of Medicine and Food Homology - Leong, May Ho; Yong, Yii Pin; Heng, Aik Teng; Wong, Pui Yee; Chai, Jia Yee (INTI International University, 2021)
Various plans for the treatment of COVID-19 were implemented by different countries. This research is a preliminary study to understand COVID-19 in Malaysia from the perspective of Chinese medicine and provide a coexistence plan. The methodology is to categorize the symptoms of COVID-19 in Malaysia under syndrome element and referred to the climatic environment toprescribe a tea that will draw up a life pattern to coexists with COVID-19. Considering that the symptoms of COVID-19 in Malaysia are fatigue, inability to swallow, and oliguria, early clinical symptoms are not obvious, but may lead to sudden death. The results showed that COVID-19 occurred in the hot and dry year of Gengzi (2020), and the increase in cases was evident in the fire and summer periods of the cold and wet Xinchou year (2021). Considering that the internal Fire is the most hurtful and the ‘Cold and Dampness’ will prevent the internal ‘Fire’ to be released to the outdside. Based on this, it is inferred that COVID-19 in Malaysia is an internal Fire, mixed with external Cold, and has been an epidemic of Cold and Fire. Based on the theory of medicine and food homology, a dose of tea is formulated to separate the internal and external parts, dispel the body surface, clear the internal fire, and smooth the mechanism to achieve coordination of the inside and outside. Through this compatible tea, it can be used as a food or as a medicine. In the two-and-a-half-day treatment plan, a total of 11 confirmed or suspected COVID-19 cases were collected from July to August, all cases partial symptom elimination, no severe cases occurred, and the complete recovery rate was 45%.